Strengthening the halal supply chain ecosystem in business unit of pesantren - Retnowati, May Shinta; Rusli, Lathiefa; Aziz, Muhammad Abdul; al Faruqi, Musta’an; Pratama, Agma Arjuna Rizky (Indonesian Journal of Islamic Economics Research, 2025)
To fulfill the halal needs of consumers or the community of Pesantren, the implementation of a Halal Supply Chain in every product is very important. Moreover, in boarding schools that offer various business units, a halal supply chain can be applied to create a halal ecosystem to foster better social change. This study is a qualitative study with a comparative approach on the objects of Darussalam Drinking Water (AMIDAS) and Khizanah Bakery (Manufacturing) and Gambia Market (Retail/Distributor), which are business units of Pondok Modern Darussalam Gontor.. The results of this study indicate that the supply chain in the PMDG business unit has been well implemented. Meanwhile, halal supply chain activities are divided into three; first, halal supply chain resources include organization, information management, physical separation, and Islamic human resources. Second, halal supply chain business processes are halal manufacturing and halal logistics. Third, the halal supply chain network for Amidas and Khizanah Gontor Bakery as producers sources materials from manufacturers, produces goods, stores them in warehouses, and distributes them to retailers, sub-retailers, and so on. Gambia as a distributor receives products from producers according to halal standards and then provides them to customers. All halal supply chain activities have been carried out in accordance with Islamic principles.